Case Report: En bloc resection of inferior vena cava and renal cell carcinoma with level IV tumor thrombus associated with tumor thrombus embolization to the pulmonary arteries: presence of blood vessels inside the tumor thrombus - Dugarte, Juan; Buitrago, Daniel H.; Nicolau-Raducu, Ramona; Raber, Joshua P.; Kaneku, Hugo; Alvarez, Angel; Ciancio, Gaetano (Frontiers in Oncology, 2025)
Renal cell carcinoma (RCC) is an aggressive kidney cancer often diagnosed at an advanced stage. This type of kidney tumor can be associated with tumor thrombus (TT), which can extend into the inferior vena cava (IVC) and, in severe cases, into the right side of the heart. Managing RCC with TT is particularly complex when extension of the TT into the right heart is present, as the use of intraoperative transesophageal echocardiography (TEE) and cardiopulmonary bypass (CPB) aid in performing a complete TT surgical resection. In terms of tumor neo-vessels, solid tumors such as RCC-TT depend on a vascularized connective tissue stroma for growth, proliferation and malformation which are supported by various factors promoting these processes. Herein, we present the case of a 69-year-old patient with a right renal tumor with a TT extending through the IVC up into the right side of the heart. During the surgery, a segment of the TT embolized into the pulmonary arteries, highlighting the surgical challenges, the use of CPB, and TEE in managing such cases, as well as discussing the implications of finding blood vessels inside the TT.